Losartan Attenuates Radiation-Induced Damage on Testes and Accelerates Tubular Regeneration - Santos, Lais L. Manção dos; Alves, Marco G.; Chies, Agnaldo Bruno; Spadella, Maria Angélica (Frontiers in Reproductive Health, 2022)
Male germ cells are particularly susceptible to radiation; infertility being a common consequence after radiotherapy as it impairs spermatogenesis. This study aimed to test whether treatment with losartan (LOS), a selective antagonist of angiotensin II receptor subtype 1 (AT1R), can prevent or attenuate the acute and long-term radiation-induced damage to testes. Wistar rats were randomly distributed into six groups, three of which were studied on day 2 after irradiation: control (CTRL 2), irradiated non-treated (IR 2), and irradiated and treated with LOS (IRLOS 2); and three other groups that were studied on day 60 after irradiation: control (CTRL 60), irradiated non-treated (IR 60), and irradiated and treated with LOS (IRLOS 60). Seven consecutive days before and on the day of irradiation with 2.5 Gy directly administered in the scrotum, the animals were treated with LOS (34 mg/kg/two times/day). This treatment was continued 2 or 60 days after irradiation. The sperm quality was assessed from epididymis cauda. In addition, the testes were submitted to histopathological and morphometric-stereological analysis as well as the proliferating cell nuclear antigen (PCNA) quantification. Serum FSH and LH and plasma testosterone levels were also determined. The data obtained 2 days after the irradiation showed germ cell apoptosis, formation of vacuoles in the seminiferous epithelium, sloughing of germ cells into the lumen, and retention and phagocytosis of step-19 spermatids in Sertoli basal cytoplasm. The treatment with LOS in this period did not prevent or attenuate a radio-induced damage to the testes, illustrating that this drug does not protect against apoptosis derived from direct effects of radiation. On the other hand, 60 days after exposure, the data evidenced the deleterious effects of ionizing radiation on the testes as decreasing of testicular, epididymal, and seminal vesicle masses; tubular atrophy; reduction of cellular proliferation; and loss of germ cells. LOS was able to prevent some of those deleterious effects, promoting improvements in seminal vesicle mass, sperm vitality, plasma testosterone levels, vacuole number, and cell proliferation. In conclusion, inhibition of the AngII/AT1R axis by LOS is effective in protecting the indirect/delayed radiation damage resulting from oxidative stress established in the tissue.